Self-cleaning and UV-blocking cotton – Fabricating effective ZnO structures for photocatalysis - Lawrynowicz, Alicja (Elsevier BV, 2025)
This study comprehensively examines the relationship between synthesis conditions that affect the morphologies of ZnO crystals and, therefore, the resulting properties of ZnO-coated self-cleaning and UV blocking textiles. Although the current literature presents several individual recipes, this study uniquely identifies and documents the impact of different processing methods and additives on crystal morphology within one complete synthesis protocol—that is, NaOH concentration, microwaving duration, and NH4OH additive quantity. Consequently, we suggest a simple and surfactant-free microwave-assisted method of forming ZnO coating with a distinctive flower-like morphology and high surface coverage, with demonstrated optimal self-cleaning performance: a solution of 66 ml of 0.1 M NaOH, 33 ml of 0.2 M of ZnAc dissolved in EtOH, and 2 ml of NH4OH microwaved for 5 min. The efficacy of ZnO-coated cotton in ultraviolet (UV) blocking was verified with UV protection factor calculations, reaching a near-complete UV blocking capability (as high as 99.93 % for UV-B). The evaluation of photocatalytic self-cleaning performance involved monitoring the discoloration of coffee and methylene blue (MB) stains under 1 Sun, using the innovative photo analysis-based method. The MB dye degradation efficiency of the best-performing samples reached 73 % within the first hour of 1 sun exposure, which is double the speed reported in related studies. The results confirm that flower-like ZnO coating, produced through our simplified protocol, is a viable option for the development of UV-resistant and self-cleaning textiles.